2006
DOI: 10.1016/j.biocon.2005.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-suitability modelling to assess the effects of land-use changes on Dupont’s lark Chersophilus duponti: A case study in the Layna Important Bird Area

Abstract: Habitat-suitability modelling is being increasingly used as a tool for conservation biology.Although studies at large spatial scales are more appropriate for reserve design and management, there is a scarcity of published work on local, high-resolution applications of such models. In this work we develop high-resolution habitat models (1 ha) and study habitat preferences (focal points) of Dupont's lark Chersophilus duponti, an endangered shrubsteppe passerine, in the partially overlapping Special Protected Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
9

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 40 publications
3
61
0
9
Order By: Relevance
“…Habitat selection studies in the same Layna páramos that include our study area (Seoane et al 2006) found that Dupont's Larks select habitat patches with about 35% cover of medium-sized shrubs (25-50cm), and similar values have been obtained by Garza & Suárez (1990) in other Spanish localities. Radio-tracking of marked individuals also in Layna páramos showed that Genista pumila, which represents nearly 60% of scrubs between 20 cm and 40 cm in our study area, accounted for 90% of locations (Garza et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Habitat selection studies in the same Layna páramos that include our study area (Seoane et al 2006) found that Dupont's Larks select habitat patches with about 35% cover of medium-sized shrubs (25-50cm), and similar values have been obtained by Garza & Suárez (1990) in other Spanish localities. Radio-tracking of marked individuals also in Layna páramos showed that Genista pumila, which represents nearly 60% of scrubs between 20 cm and 40 cm in our study area, accounted for 90% of locations (Garza et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…One important difference between these ecosystems and our study area is that they are dominated by grasslands, which recover faster than scrubs as our results for the second spring after fire have shown. However, as stated previously, in Spain a continuous grass cover is sub-optimal for the species that also selects for some percentage of bare ground (Seoane et al 2006). In this country just a few populations of Dupont's Lark inhabit alpha grass Stipa tenacissima steppes while most North African populations (90%) are located in areas of this vegetation type (García et al 2008, Suárez 2010.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Maiorano et al 2006;Rondinini et al 2006;Zielinski et al 2006;Tapia et al 2007) or assess the effects of environmental changes (e.g. Berry et al 2002;Thuiller 2003;Araú jo et al 2004;Puglisi et al 2005;Seoane et al 2006). For this reason, habitat suitability models (HSMs) have been increasingly used in the last decades.…”
Section: Introductionmentioning
confidence: 99%